A cluster onset of acute and accelerated silicosis cases in workers of ramming mass industries in Jharkhand, Eastern India - Dharmendra Singh; Samit Kumar Carr; Bidisa Sarkar; Syed Irfan Ali; Kamalesh Sarkar (Journal of Family Medicine and Primary Care)
Introduction and Methodology: A cross-sectional study was conducted among workers of ramming mass industries in the East Singhbhum district of Jharkhand, eastern India. Workers had occupational exposure to respirable crystalline silica dust of varied duration between 1 and 6 years. A total of 122 subjects participated in it. Relevant epidemiological information was collected from them. All were x-rayed using 300 mA radiation for the detection of the presence of silicotic opacities if any as described by the International Labour Organisation (ILO) for the detection of silicosis. Results: The study revealed that 61.4% (n = 75) of subjects had silicosis. Of them, 19 had acute silicosis (having a duration of silica dust exposure of 2 years or lesser) and 56 had accelerated silicosis (a duration of occupational exposure of > 2 to 6 years). The offending agent was clouds of respirable crystalline silica dust from the ramming mass industries. Epidemiological Interpretation: To the best of our knowledge, this is the first report of an outbreak of acute and accelerated silicosis cases because of occupational inhalational exposure to ramming mass in India with a sizable portion of female workers with silicosis. Regional as well as national authorities need to take appropriate interventional measures in a programmatic mode as soon as possible. Conclusion: An in-depth investigation on the existence and magnitude of the problem of silico-tuberculosis is needed to be performed in them as silicosis increases the vulnerability of pulmonary tuberculosis among the affected workers.